2019
DOI: 10.6118/jmm.19193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Supplementary Vitamin D on Bone Mineral Density When Used in Combination with Selective Estrogen Receptor Modulators

Abstract: Objectives Vitamin D is regarded as one of the major nutrients that significantly influence bone metabolism. This study aims to look at the effect of supplementary vitamin D on bone mineral density (BMD) in female osteoporosis patients. Methods The retrospective hospital record review was performed on 282 patients who were diagnosed with osteoporosis and treated with selective estrogen receptor modulators (SERMs) between January 2015 and December 2016. Of these patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Reid et al [27] insisted that the benefit of using vitamin D to improve BMD is questionable. However, Liu et al [28] suggested that the SERMs with vitamin D may have some additive effect on improving BMD. However, there are a few reports that assess the effect of SERMs with vitamin D. In this study, SERMs with vitamin D tended to have https://doi.org/10.11005/jbm.2022.29.3.185 a larger increase of BMD than SERMs monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Reid et al [27] insisted that the benefit of using vitamin D to improve BMD is questionable. However, Liu et al [28] suggested that the SERMs with vitamin D may have some additive effect on improving BMD. However, there are a few reports that assess the effect of SERMs with vitamin D. In this study, SERMs with vitamin D tended to have https://doi.org/10.11005/jbm.2022.29.3.185 a larger increase of BMD than SERMs monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Raloxifene has been shown to increase lumbar spine BMD and reduce fracture risk in patients with osteoporosis, with a recent study demonstrating additional BMD improvement when it is given in combination with cholecalciferol. 11 , 12 Furthermore, the drug may be more widely prescribed in clinical practice given its superior safety profile when compared with bisphosphonates, particularly in the context of medication-related osteonecrosis of the jaw and atypical femoral fracture. 13 , 14 Raloxifene has an advantage over combined estrogen and progestin therapy in reducing the risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%